2018
DOI: 10.1177/1557988318763522
|View full text |Cite
|
Sign up to set email alerts
|

“Boy Crisis” or “Girl Risk”? The Gender Difference in Nonsuicidal Self-Injurious Behavior Among Middle-School Students in China and its Relationship to Gender Role Conflict and Violent Experiences

Abstract: Purpose:We attempted to test if there were gender differences in nonsuicidal self-injurious (NSSI) behaviors among Chinese middle-school students, and analyze the impact of gender role conflict and violent experiences on these behaviors among middle-school students of different genders.Method:Based on the survey data from seven middle schools in Xi’an region of China, the gender difference in NSSI behaviors and its associated factors were analyzed in this study.Results:There was no significant gender differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
5
10
1
Order By: Relevance
“…The results revealed that the prevalence of NSSI behaviors was similar among both males (17.2%) and females (19.4%), yet no significant gender difference was found. This finding is consistent with studies in other contexts [ 9 , 69 ]. Existing studies in western countries stated that the gender difference in the prevalence of NSSI among clinical samples is more signicant than that in community samples [ 54 ], but our analysis results are different: there is no gender difference in the prevalence of NSSI among clinical samples.…”
Section: Discussionsupporting
confidence: 94%
“…The results revealed that the prevalence of NSSI behaviors was similar among both males (17.2%) and females (19.4%), yet no significant gender difference was found. This finding is consistent with studies in other contexts [ 9 , 69 ]. Existing studies in western countries stated that the gender difference in the prevalence of NSSI among clinical samples is more signicant than that in community samples [ 54 ], but our analysis results are different: there is no gender difference in the prevalence of NSSI among clinical samples.…”
Section: Discussionsupporting
confidence: 94%
“…From the descriptive results, the prevalence of NSSI among male students is 37.6% and that of female students is slightly higher (39.1%) than that of male students, which is not only higher than the survey results of Western countries (Burke et al, 2015; Ross & Heath, 2002; Whitlock, et al, 2007a, b), but higher than the survey results among Chinese middle school students (Wang & Wang, 2009; Xiao et al, 2008), but gender difference did not show too much significance. This finding is consistent with the conclusion of Yang, indicating that the hypothesis of “boy crisis” or “girl risk” of NSSI behavior of middle school students in China has not yet been confirmed (Yang & Xin, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…The results revealed that the prevalence of NSSI behaviors was similar among both males (17.2%) and females (19.4%), yet no signi cant gender difference was found. This nding is consistent with studies in other contexts [71,72]. Existing studies in western countries stated that the gender difference in the prevalence of NSSI among clinical samples is more signicant than that in community samples [56], but our analysis results are different: there is no gender difference in the prevalence of NSSI among clinical samples.…”
Section: Discussionsupporting
confidence: 90%